The outer reaches of life - Postgate, J. R. (John Raymond) (Cambridge : Cambridge University Press, 1994)
Since the dawn of life on Earth, the world has been gradually transformed by living things into a comfortable home for plants, animals and ourselves. But many harsh and seemingly inhospitable places remain, and it is the inhabitants of such places, mainly invisible microbes, that reveal the remarkable potential and resilience of life itself. How do microbes survive, even flourish, in superheated water or supercooled brine; at enormous pressures; without air; amid poisons?
And what part do, and did, they all play in making the Earth hospitable?
In this fascinating account, for lay readers, John Postgate, one of Britain's leading microbiologists, tells of the diverse adjustments microbes have made to apparently impossible habitats.
Modern understanding provides new clues to the origin and evolution of terrestrial life, offers glimpses of how life might have established itself elsewhere in the universe, and raises profound questions about death, sensation and individuality - as well as illustrating the often muddled pathways of scientific progress.
1. Microbes and terrestrial life -- 2. Some like it hot -- 3. Cool, man, cool -- 4. The big squeeze -- 5. A salty tale -- 6. Corrosive and slippery places -- 7. Life without oxygen -- 8. Living on minerals -- 9. Exotic menus -- 10. Of wraiths and ghosts -- 11. The inertness of nitrogen -- 12. Getting about -- 13. Microsenses -- 14. A private space -- 15. Company -- 16. Immortality and the Big Sleep -- 17. Self-adjustment -- 18. Life's outer reaches.
Keywords: Extreme environments -- Microbiology; Microorganisms